The rediscovery of Buffon’s “Guarouba” or “Perriche jaune”: two senior synonyms of Aratinga pintoi Silveira, Lima & Höfling, 2005 (Aves: Psittaciformes) - Nemésio, André; Rasmussen, Claus (Zootaxa, 2009)
Buffon’s “Guarouba” or “Perriche jaune” is illustrated in his magnificent “Histoire Naturelle des Oiseaux” and was interpreted by Buffon as the same bird described by Marcgrave in the 17th century as “Guarouba” or “Quijubatui”. Nevertheless, the bird described by Marcgrave corresponds to the species formally described by Gmelin (1789) as Psittacus guarouba and currently known as Guarouba guarouba. Buffon’s bird was named Psittacus luteus Boddaert, 1783, became the type-species of the genus Aratinga, and has long been considered a junior synonym of Psittacus solstitialis Linnaeus, 1758 (now Aratinga solstitialis). However, Buffon’s illustration, upon which the description of P. luteus Boddaert, 1783 was based, is not an Aratinga solstitialis, but a similar species recently redescribed and named Aratinga pintoi Silveira, Lima & Höfling, 2005. An earlier, although long overlooked, older synonym of P. luteus, is Psittacus maculatus Statius Müller, 1776, also based on Buffon’s plate, and which turns out to be the valid nomen of this species. Thus, Aratinga maculata (Statius Müller, 1776) comb. nov. is the senior synonym of both Psittacus luteus Boddaert, 1783 syn. nov. and Aratinga pintoi Silveira, Lima & Höfling, 2005 syn. nov. In order to establish nomenclatural stability, the holotype of Aratinga pintoi is here designated as neotype of both Psittacus maculatus and Psittacus luteus, establishing an objective synonymy among the three nomina.